Estudo taxonômico de Mecistogaster Rambur, 1842 e Platystigma Kennedy, 1920 da Mata Atlântica (Odonata: Pseudostigmatidae) - Déborah Souza Soldati Lacerda (2017)
The pseudostigmatid damselflies from the Atlantic Forest of Brazil are studied based on 242 specimens from various scientific institutions. The study allowed the revalidation of the genus Platystigma, which has been previoulsy synonymized with Mecistogaster. The two genera differ mainly by the penis segment 3, which is a flagellum in Mecistogaster and plate-like in Platystigma. The two species of Platystigma from the Atlantic Forest, P. astictum and P. pronoti are redescribed. Emphasis is given to the utilization of two structural character hitherto never used before in Pseudostigmatidae taxonomy: anterior hamule and female epiproct. Four new species (Mecistogaster eustaquioi n. sp., M. jacatinga n. sp., M. kesselring n. sp. and M. mielkei n. sp.) are described and illustrated, based mainly on penis structure, anterior hamule morphology and color of the mesepimeron. Sex association of Mecistogaster kesselring was done, based on a couple found in copula.The taxonomic status of Mecistogaster amalia is discussed; its holotype, supposed to be in Halle Museum, is actually lost. The M. amalia specimens described by Selys and all other identified according to his description do not correspond to Burmeisters original description and, therefore, do not belong to M. amalia. A study of the oviposition behavior in Platystigma and a possible correlation between the structure of lateral valve of ovipositor and the type of oviposition were presented.